High-Definition Video Recording: Taking Sport Technology to the Operating Room - de Sierra, C. Velasco Garcia; Estevez-Cid, F.; Cuenca-Castillo, J. J. (The Thoracic and Cardiovascular Surgeon, 2018)
Filming surgeries for teaching purposes, publications, and patient records has become increasingly popular as the systems for digital recording have evolved, becoming high-quality systems, both smaller and lighter. Digital recording allows long-term storage, retrieval, and database organization. In addition, sharing digital contents has also become easier since video sharing sites and social networks make it possible to upload these contents onto the Internet. We describe a simple and economical system for surgeons to record surgeries in high definition under sterile conditions without any interference with the surgeon's line of vision.
Keywords: cardiac; surgery/incisions/exposure/techniques